Perencanaan dan Perancangan Terminal Penumpang Pelabuhan Kalianget Dengan Pendekatan Eco-Tech Architecture - Rizal Fandani (Prosiding Sains dan Teknologi, 2022)
The passenger terminal is a very needed facility for the community or tourists in Sumenep Regency, because of the conditions in the field that already have a port but do not have adequate terminal facilities. Passengers who have always been faced with discomfort when waiting for ships to dock and also the emergence of a negative stigma in society that the port is a slum place that raises issues that must be resolved immediately. The design of the passenger terminal at Kalianget port, Sumenep Regency is closely related to architectural principles by applying a combination of ecological concepts and architectural technology. The purpose of this design is to produce a Kalianget Port Passenger Terminal Design that can increase the number of users and tourists who will visit the surrounding islands. The benefits of this design are that it can improve the economy, the image of the region and create jobs for the surrounding community as well as eliminate the bad stigma in the community regarding slum ports. This design uses an Eco-Tech Architecture approach, where this theme is very suitable to be applied because the surrounding area is very supportive of the implementation of 6 principles in Eco-Tech architecture. where in general this concept has the aim of maintaining each other between the artificial environment and the natural environment. Keywords: Kalianget Harbor, Port Passenger Terminal, Eco-Tech Architecture